Life satisfaction in patients with temporomandibular disorders - Marczak, Milena; Ginszt, Michał; Berger, Marcin (Journal of Education, Health and Sport, 2017)
Introduction: Temporomandibular disorders (TMD) are abnormal, fixed and harmful motor dysfunctions affecting teeth, temporomandibular joints, ligaments, and muscles. TMD influences the patient's daily activities and quality of life by experiencing a chronic pain syndrome. Other symptoms accompanying TMD are psychological factors such as stress and anxiety. Aim: The aim of the study is to describe the difficulties in activities of daily living in patients with TMD, affecting the quality of life. Material and methods: The attempt was made to describe the difficulties in activities of daily living in patients with TMD. Using keywords "life satisfaction" and "temporomandibular disorders" we performed a review of relevant articles based on a PubMed and Google Scholar search, focusing on the last ten years. Results and discussion: TMD cause limitation of patients' daily functioning due to pain experienced. As abnormal and fixed motor dysfunction, they affect the limitation in interpersonal communication, the expression of emotions, and the intake of food. This results in a subjective feeling of dissatisfaction with life that limits the fulfillment of life's aspirations in personal and professional life. Conclusions: The systematization of knowledge about the influence of physiological and psychological variables on quality of life in patients with TMD, taking into account the direct influence of individual factors and their collective effects, seems to be significant and requires further research. In addition, it is important to include psychological therapy, including the cognitive and emotional functioning of the patient, for the treatment of TMD.